2022
DOI: 10.1155/2022/6079241
|View full text |Cite
|
Sign up to set email alerts
|

College Students with Oral Habits Exhibit Worse Psychological Status and Temporomandibular-Related Quality of Life: A Correlational Study

Abstract: Purpose. To evaluate the relationship between oral habits, psychological status, and temporomandibular-related quality of life among college students. Materials and Methods. An online questionnaire was sent to college students who were willing to participate in this anonymous survey, which contained questions about the demographic characteristics of the participants, the Patient Health Questionnaire for Depression and Anxiety (PHQ-4), the Fonseca Anamnestic Index (FAI), and the Oral Health Impact Profile for t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 28 publications
0
3
0
Order By: Relevance
“…The third part is the Patient Health Questionnaire-4 (PHQ-4) [ 20 ], which has been used in our previous studies [ 5 , 21 ]. A 4-point Likert scale ranging from 0 (not at all) to 3 (nearly every day) is used.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The third part is the Patient Health Questionnaire-4 (PHQ-4) [ 20 ], which has been used in our previous studies [ 5 , 21 ]. A 4-point Likert scale ranging from 0 (not at all) to 3 (nearly every day) is used.…”
Section: Methodsmentioning
confidence: 99%
“…Study has revealed that TMDs are the leading causes of chronic pain in the temporomandibular region, with a prevalence in the general population at 10–31% [ 2 4 ]. Moreover, TMDs, particularly pain-related TMDs, are widely recognized for impairing both oral health-related and overall quality of life [ 5 , 6 ].…”
Section: Introductionmentioning
confidence: 99%
“…Parafunctional habits referred to poor habits associated with TMD, such as unilateral chewing, biting hard foods, etc. 26 …”
Section: Methodsmentioning
confidence: 99%